2008
DOI: 10.1002/macp.200800077
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Effects of Hydrophilic Branch Size, Distribution, and Connectivity in Amphiphilic Polyethylene

Abstract: Acyclic diene metathesis (ADMET) polymerization/hydrogenation methodology was used to synthesize a family of amphiphilic polyethylenes (PEs) with precisely placed poly(ethylene glycol) branches. Four structural parameters are varied in this report: size of the hydrophilic pendant group, manner in which the pendant group is connected to the backbone, distance between the pendant moieties along the backbone, and saturation of the polyolefin backbone. Varying the branch size with other parameters held constant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…In contrast, the saturated version of polymers showed a glass transition at −79 °C to −57 °C and endothermic peaks at −3.3 °C to −11 °C. Similar behavior is observed for the regularly branched precision LLDPEs, which were synthesized by the ADMET polymerization, reported by Wagener et al Additionally, a broad exothermic peak was observed between the glass transition and the endothermic peak. We speculate that the broad exothermic peak is attributable to the low-temperature crystallization of polymers, which are in a supercooled state, whereas the endothermic peak is due to melting of the crystallized polymers.…”
Section: Resultssupporting
confidence: 82%
“…In contrast, the saturated version of polymers showed a glass transition at −79 °C to −57 °C and endothermic peaks at −3.3 °C to −11 °C. Similar behavior is observed for the regularly branched precision LLDPEs, which were synthesized by the ADMET polymerization, reported by Wagener et al Additionally, a broad exothermic peak was observed between the glass transition and the endothermic peak. We speculate that the broad exothermic peak is attributable to the low-temperature crystallization of polymers, which are in a supercooled state, whereas the endothermic peak is due to melting of the crystallized polymers.…”
Section: Resultssupporting
confidence: 82%
“…30a). 111 The results of this study showed that the PEG branches induced folds in the backbone, resulting in small paraffin-like crystallites composed of the methylene sequences between branches (Fig. 30b).…”
Section: Ethylene Copolymers Through Admet Polymerisationmentioning
confidence: 74%
“…30 (a) Different ADMET derived polyethylenes containing perfectly spaced hydrophilic PEG branches and (b) chain folding and crystallisation of the ADMET derived amphiphiles. 111 moieties along the backbone, and the saturation of the polyolefin backbone (Fig. 30a).…”
Section: Ethylene Copolymers Through Admet Polymerisationmentioning
confidence: 99%
“…Significant progress has been accomplished in understanding these strictly alkyl functional, and similar effort has been undertaken in more functional PE polymers. As polar group incorporation into a hydrophobic backbone has shown to improve particular properties such as impact resistance and polymer adhesion, but also as chemical barriers, the catalyst developments underlying the ADMET polymerization chemistry here give rise to nearly limitless options with regard to drawing functional groups from the period table ranging from metals67–70 to halogens71–73 and various ether,74–78 ester,79–84 acid,85–87 and ionic88–90 functionality.…”
Section: Admet Evolutionmentioning
confidence: 99%